Accelerated calvarial healing in mice lacking Toll-like receptor 4. - Dan Wang; James R Gilbert; James J Cray; Adam A Kubala; Melissa A Shaw; Timothy R Billiar; Gregory M Cooper (PLoS ONE, 2012)
The bone and immune systems are closely interconnected. The immediate inflammatory response after fracture is known to trigger a healing cascade which plays an important role in bone repair. Toll-like receptor 4 (TLR4) is a member of a highly conserved receptor family and is a critical activator of the innate immune response after tissue injury. TLR4 signaling has been shown to regulate the systemic inflammatory response induced by exposed bone components during long-bone fracture. Here we tested the hypothesis that TLR4 activation affects the healing of calvarial defects. A 1.8 mm diameter calvarial defect was created in wild-type (WT) and TLR4 knockout (TLR4(-/-)) mice. Bone healing was tested using radiographic, histologic and gene expression analyses. Radiographic and histomorphometric analyses revealed that calvarial healing was accelerated in TLR4(-/-) mice. More bone was observed in TLR4(-/-) mice compared to WT mice at postoperative days 7 and 14, although comparable healing was achieved in both groups by day 21. Bone remodeling was detected in both groups on postoperative day 28. In TLR4(-/-) mice compared to WT mice, gene expression analysis revealed that higher expression levels of IL-1β, IL-6, TNF-α,TGF-β1, TGF-β3, PDGF and RANKL and lower expression level of RANK were detected at earlier time points (≤ postoperative 4 days); while higher expression levels of IL-1β and lower expression levels of VEGF, RANK, RANKL and OPG were detected at late time points (> postoperative 4 days). This study provides evidence of accelerated bone healing in TLR4(-/-) mice with earlier and higher expression of inflammatory cytokines and with increased osteoclastic activity. Further work is required to determine if this is due to inflammation driven by TLR4 activation.